Environment change causes a transient adverse impact on horse behavioral resting patterns - Oliveira, Tiago M.; Zanotto, Gustavo M.; Trindade, Pedro H.E. [UNESP]; Baccarin, Raquel Y.A. (Elsevier, 2025)
The influence of the environment on resting patterns in horses is not completely understood. We aimed to investigate if the behavioral resting patterns of sports horses change from their home environment to a hospital environment because we hypothesized that moving to a hospital environment might negatively impact the horses' resting patterns. Eight Quarter horses were recorded for three days in their home environment to determine the baseline resting pattern, for five days at the Teaching Hospital of the University, and for a further three days following their return to their home environment. The latency for each horse performance the first sternal and lateral recumbency was computed and compared between the hospital and home environment post-hospitalization. The frequency and duration of sternal and lateral recumbency were lower on the days of hospitalization compared with the baseline (p < 0.05). The frequency and duration of sternal and lateral recumbency were returned to baseline values on the first night of their return to their home environment. The latency for the first sternal and lateral recumbency was higher in the hospital environment than in the home environment post-hospitalization. These behavioral resting pattern changes might be understood as transitory because it returned to the baseline pattern on the first night when horses returned to their home environment. In conclusion, the horses investigated in this initial study decreased their resting behaviors when hospitalized for five days. Future studies are necessary to enlarge the sampling size and quantify the impact of this resting behavior reduction on the horses’ quality of life.
Keywords: Recumbency; Rest; Sleep; Sports horses